Accelerometers for the assessment of concussion in male athletes: A systematic review and meta-analysis - Brennan, J. H.; Mitra, B.; Synnot, A.; McKenzie, J.; Willmott, C.; McIntosh, A. S.; Maller, J. J.; Rosenfeld, J. V. (Sports Medicine, 2017)
Concussion is common in the sporting arena and is often challenging to diagnose. The development of wearable head impact measurement systems has enabled measurement of head kinematics in contact sports. Objectives: The objective of this systematic review was to determine the characteristics of head kinematics measured by an accelerometer system among male athletes diagnosed with concussion. Methods: A systematic search was conducted in July 2015. Inclusion criteria were English-language studies published after 1990 with a study population of male athletes, in any sport, where objectively measured biomechanical forces were reported in the setting of a concussive event. The random effects meta-analysis model was used to combine estimates of biomechanical force measurements in concussed athletes. Results: Thirteen studies met the inclusion criteria, the majority of which were conducted with high school and college football teams in the US. Included studies measured a combination of linear and rotational acceleration. The meta-analysed mean peak linear head acceleration associated with a concussive episode was 98.68 g (95 % CI 82.36-115.00) and mean peak rotational head acceleration was 5776.60 rads/s2 (95 % CI 4583.53-6969.67). The estimates of the biomechanical forces were consistent across studies, with I2 values of 0 % for both meta-analyses. Conclusions: Head impact monitoring through accelerometery has been shown to be useful with regard to characterising the kinematic load to the head associated with concussion. Future research with improved clinical outcome measures and head kinematic data may improve accuracy when evaluating concussion, and may assist with both interpretation of biomechanical data and the development and utilisation of implementation strategies for the technology.